A Dual-Mode Bandpass Filter with Multiple Controllable Transmission-Zeros Using T-Shaped Stub-Loaded Resonators - Zh. Yao; C. Wang; N. Y. Kim (The Scientific World Journal)
A dual-mode broadband bandpass filter (BPF) with multiple controllable transmission-zeros using T-shaped stub-loaded resonators (TSSLRs) is presented. Due to the symmetrical plane, the odd-even-mode theory can be adopted to characterize the BPF. The proposed filter consists of a dual-mode TSSLR and two modified feed-lines, which introduce two capacitive and inductive source-load (S-L) couplings. Five controllable transmission zeros (TZs) can be achieved for the high selectivity and the wide stopband because of the tunable amount of coupling capacitance and inductance. The center frequency of the proposed BPF is 5.8 GHz, with a 3 dB fraction bandwidth of 8.9%. The measured insertion and return losses are 1.75 and 28.18 dB, respectively. A compact size and second harmonic frequency suppression can be obtained by the proposed BPF with S-L couplings.